MOTIVASI WISATAWAN MENGUNJUNGI OBJEK WISATA DI DESA PAWAN KABUPATEN ROKAN HULU - Nanang Rudi Harsono; Firdaus Yusrizal (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Motivation is the force that drives someone to do something to achieve the goal. These forces are basically stimulated by their various needs. The need is the reason tourists visit in the tourist attraction. This study aims to find out what the motivation for travelers visiting the attractions in the village pawan Rokan Hulu. This study used a qualitative method with descriptive approach to address issues. For the purposes of the first use of the interview, and for the second goal in using Cross Tabulation techniques. The sample in this study were 60 respondents, taken using accidental sampling. While data collection techniques in this study using observation, questionnaire, interview and documentation. By using a Likert scale as a measure to determine the length of the short interval. Motivation can be grouped into four major sub groups motivational variables physical, cultural motivation, social motivation, and Fantasi.Mclntosh 1977 murphy Sharpley 1985 and 1994 (in Pitana and Gayatri 2005: 59. By indicator relaxation, health, looking for comfort, sports activities, learn the customs, know the traditions, learn the culture, see the art, stay in touch relatives, maintaining prestige, got hospitality, refuge, looking for fantasy, enjoy the satisfaction, seeking status, seeking freedom. From the results of research conducted in the field of research on motivation tourists visiting the attractions in the village of the district pawan rokan upstream result most dominant motivation is motivation fantasyKeywords: Motivation Travellers, Attractions, Village Pawan